Positive and extensive intergroup contact in the past buffers against the disproportionate impact of negative contact in the present - Paolini, Stefania; Harwood, Jake; Rubin, Mark; Husnu, Shenel; Joyce, Nicholas; Hewstone, Miles (Wiley-Blackwell, 2014)
Negative (vs positive) intergroup contact may have a disproportionately large impact on intergroup relations because of valence-salience effects, whereby negative contact causes higher category salience (Paolini, Harwood, & Rubin, 2010). One correlational and three experimental studies in three conflict areas (Northern Ireland, Arizona's border area, and Cyprus; Ns=405, 83, 76, and 91) tested the moderation of these valence-salience effects by individuals' histories of outgroup contact. Consistent with a perceived fit principle valence-salience effects of face-to-face, television-mediated, and imagined contact held among individuals with negative or limited histories of outgroup contact; these effects were significantly reduced or nonsignificant among individuals with positive or extensive past outgroup contact. These moderation effects suggest that positive and diverse intergroup contact in the past buffers against the harmful effects of negative contact experiences in the present, thus limiting the potential for negative spiralling of intergroup relations. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: Social-Cognitive Theory; Extended Contact; Interracial Contact; Outgroup Attitudes; Racial Prejudice; Northern-Ireland; Categorization; Individuals; Reduction; Salience